Própolis no controle da mastite bovina - Peixoto, Erika Cosendey Toledo Mello; Jardim, Julia Gazzoni; Heinzen, Eduardo Luiz; Domingues, Paulo Francisco [UNESP]; Padovani, Carlos Roberto [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (My University, 2012)
Bovine mastitis is considered the main disease causing great economic losses in dairy herds. It is usually treated by antimicrobial chemicals that promote drug resistance, residues in food and environmental contamination. However, consumers in different countries requires more natural foods and with higher quality. Thus, the objective was to check the activities of propolis in controlling bovine mastitis. Seventy-two Holstein cows were used. The mastitis was identified by the California Mastitis Test, somatic cell counts and microbiological examination of milk. Four treatments were held: in group EAP1 10ml of a 30% alcoholic propolis extract (EAP) were given orally for seven consecutive days; in group EAP2 the same procedure described for the first group was used, in addition EAP was used for immersion of the teats before and after milking; in group CA alcohol was used for immersion of the teats before and after milking; and in group CT animals were subjected to soaking and disinfection, procedures routinely used by the property. The results were analyzed by the non-parametric variance model for repeated measures complemented by independent groups in multiple comparisons. There was a decrease of the somatic cell count in all groups. The biological activities of propolis provide great prospects; however, under the conditions evaluated, it was not possible to observe differences between treatments. The great diversity in its chemical composition and the complexity of multiple synergistic mechanisms involved in its biological activity require additional clinical trials.
Propolis in the control of bovine mastitis
Keywords: Agroecology; Biotherapies; Milk; Organic production